Gastric Perforation and Pancreatitis Manifesting after an Inadvertent Nissen Fundoplication in a Patient with Superior Mesenteric Artery Syndrome. (27th August 2009) - Petrosyan, Mikael; Estrada, Joaquin J.; Giuliani, Stefano; Williams, Monica; Rosen, Heather; Mason, Rodney J.
Abstract : Superior mesenteric artery (SMA) syndrome is an uncommon but well-recognized clinical entity. It can lead to proximal small bowel obstruction and severe morbidity and mortality in lieu of late diagnosis and concomitant existing comorbidities. We report a 54-year-old female, with SMA syndrome which manifested itself after Nissen fundoplication along with two major complications. The diagnosis of SMA was established by clinical symptoms and radiological findings.